PERAN MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKANKEPUASAN KERJA KARYAWAN: STUDI KAJIAN LITERATUR - AAN PRAYUDA; NUR ISNAH; IRMA; RESKY TANDIRAPAK; CHRISDAYANTI BR. GINTING (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This literature review examines the role of Human Resource Management (HRM) in enhancing employee job satisfaction. The problem addressed is how HRM practices contribute to improving employee satisfaction levels in organizations. Using systematic literature review methodology, this study analyzes various academic publications on HRM practices and job satisfaction. The findings indicate that key HRM practices including recruitment and selection, training and development, performance appraisal, compensation management, and career development significantly influence employee job satisfaction. The discussion reveals that organizations implementing comprehensive HRM strategies experience higher satisfaction levels among employees. The implications of this study suggest that organizations should integrate strategic HRM practices to foster positive work environments and enhance employee retention. This research contributes to understanding the relationship between HRM functions and employee satisfaction outcomes.